A3.18 Synovial Fibroblasts Inhibit Inflammatory T Cell Responses through Tryptophan Metabolism. (25th February 2013) - Tykocinski, Lars-Oliver; Lauffer, Anna-Marie; Bohnen, Antonia; Krienke, Stefan; Oezen, Iris; Litzenburger, Ulrike; Platten, Michael; Lorenz, Hanns-Martin
Abstract : Background and Objectives: It has been more and more accepted that fibroblasts participate in a dynamic interplay with other cells. Fibroblasts recruit immune cells and are able to influence their differentiation, proliferation, activation and survival. The development of rheumatoid arthritis (RA) is linked to functional changes of synovial fibroblasts (SFb) and a local infiltration of inflammatory cells, including B- and T cells. So far, little is known about the interaction of SFb and T cells. Here, we analysed the influence of normal SFb on the activation, proliferation and cytokine production of T cells in vitro. Materials and Methods: SFb were isolated from synovectomy tissue of patients with osteoarthritis. CD4+ T cells were stimulated with PHA and interleukin (IL)-2 in the presence or absence of fibroblasts, in direct contact or separated by a transwell chamber; their proliferation was measured by 3 H-thymidine incorporation or by PKH-26 staining. Cytokine secretion was quantified by ELISA. Surface marker expression was analysed by flow cytometry and mRNA levels of matrix metalloprotease (MMP) 1, MMP3 and Indoleamine 2, 3-dioxygenase (IDO) were quantified by real-time PCR. IDO activity was measured by kynurenine levels detected by HPLC and blocked by 1-methyl-L-tryptophan. Results: SFb strongly reduced the proliferation of activated CD4+ T cells and the secretion of pro-inflammatory cytokines like interferon (IFN)-gamma, tumour necrosis factor (TNF)-alpha or IL-17. The suppression was consistent even when the T cells were separated by a transwell membrane. Interestingly, to produce suppressive mediators the SFb first needed to be stimulated by soluble factors released by activated T cells. The dynamic interplay between T cells and SFb was also shown by the fact that the SFb support the activation of T cells at early time points of coculture. The coculture induced the expression of MMP1 and MMP3, as well as IDO mRNA and the production of nitric oxide (NO) by the SFb. Blockade of IDO, but not of MMPs or iNOS, completely abrogated the suppression of T cells, indicating that the inhibitory effect of the fibroblasts is mediated by tryptophan metabolism. Conclusions: Secreted products of activated T cells induce IDO expression in SFb which in turn leads to decreased proliferation and cytokine production of the activated T cells. This intercellular mechanism may play an important role in preventing inappropriate T cell activation and in the termination of immune reactions. The insights gained from this study may help to define the malfunctions of pathogenic SFb of RA patients.